Numerical modeling of lathanide-ion doped fibre lasers operating within mid-infrared wavelength region - Sójka, L.; Furniss, David; Tang, Zhuoqi; Sakr, H.; Barney, Emma R.; Benson, Trevor M.; Seddon, Angela B.; Sujecki, S.; Scholle, K.; Lamrini, S.; Fuhrberg, P. (2016)
We discuss the numerical modelling of lanthanide-ion doped chalcogenide glass fibre lasers for operation in the mid-infrared wavelength region. We extract the modelling parameters from emission and absorption measurements using Judd-Ofelt and McCumber theory. Numerical algorithms are developed based on the experimentally extracted fibre parameters. The simulation results predict lasing with slope efficiency of at least 20 % provided, that the fibre loss can be kept at the level of 1 dB/m or less.